Writing a pictorial essay - Peh, W.C.G.; Ng, K.H. (Singapore Medical Assoc, 2010)
A pictorial essay is a type of educational article that aims to provide both textual and visual portrayals of a topical issue. It usually consists of a short unstructured abstract, brief introduction, subheadings to organise the material and a summary. The number of references is limited to a few key articles, typically, eight to 15, or fewer. The text is usually short, often approximately 1,000 to 2,000 words in length, with much of the message contained in the figure legends. This type of article allows for a large number of figures, typically up to 20 figures or 30 figure parts. The main criteria for publication are currency, educational value and high quality of illustrations.